Analisis Jaringan Bisnis Dalam Meningkatkan Penjualan di Toko Jeep Aquascape & Aquarium - Resya Dwi Marselina; Siti Nuraena; Risma Yanti; Dede Moch Fadil Amrullah; Ulan H U Salamah; Herni Apriani; Evi Ulviah; Siti Nurkhadijah (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research employs a qualitative method to analyze and evaluate the business network of Jeep Aquascape & Aquarium stores, with a specific focus on marketing and promotional strategies. The primary objective is to identify aspects of the business network where Jeep Aquarium can redevelop its marketing and promotion strategies to address revenue instability, despite the store generally experiencing profitability. The qualitative approach involves in-depth interviews with various stakeholders, including store owners, employees, and customers. Data analysis aims to uncover patterns of revenue instability, assess the success and shortcomings of current marketing strategies, and identify internal and external factors influencing revenue fluctuations. Findings reveal that, while the store generally sees profits, attention is required to address revenue instability. Strategic recommendations from qualitative analysis include the development of more proactive promotional strategies, notably leveraging social media to reach a broader target audience. A profound understanding of business resources contributing to revenue fluctuations is also disclosed, providing additional insights for sustainable improvements. Therefore, more proactive promotions, particularly through social media, are identified as a key element to enhance visibility and customer appeal, ultimately contributing to achieving better revenue stability.